A JURIDICAL ANALYSIS OF CORAL REEF CONSERVATION STRATEGIES IN DERAWAN ISLANDS - Tarigan, Muhammad Insan; Tirtamulia, Tjondro (Universitas Bengkulu, 2024)
Berau Regency are an area of highly diverse and endangered coral reefs. Coral reefs play a very important role in the life of the marine environment. Therefore, the purpose of this research is to explore the legal basis that can protect the sustainability of coral reefs both at the international, national and local levels as well as the legal basis that guarantees the empowerment of local communities in the protection of coral reefs. The different approaches and international agreements that have been positively applied to ensure the protection of the marine environment and have bound the different countries. This article is written with normative legal research that prioritizes statutory approach and conceptual approach. In the end, it is found that Indonesia has bound itself to several international agreements that can be used as a legal umbrella in regulating the protection of coral reefs through national law. Indonesian legal instruments are heavily influenced by international law and policy. In fact, the Berau Regency Government has issued a regional regulation to maintain the quality of coral reefs in the Derawan Islands as an effort to meet and achieve marine conservation goals set at the global level. The legislation framework in Derawan has ensured community participation in the protection of maritime habitats, including coral reefs. However, there is no legal instrument that specifically and comprehensively regulates the conservation work of coral reef at the national level. Keywords: Coral Reefs; Legal Protection; SDGs.